ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF BIOACTIVE COMPOUND FROM SEMELE CORDIFORMIS - Sulastrianah, Sulastrianah; Fathan Rasyid ,; Clara M. Tumanan ,; Hartati, Hartati; I P. Sudayasa , (Journal of Innovation Research and Knowledge, 2024)
Marine biodiversity of South East Sulawesi has been used by local communities for medication since a long time ago. One of which is Semele cordiformis or ‘tude bombang’ in local languages. The community believes that the hot water extract of S. cordifirmis can help to cure hepatitis. But this has not been proven scientifically. The purpose of this study is to evaluated antibacterial and antifungal activity of S. Cordiformis as a pilot project to explore the bioactivity of this biota. Method: Antibacterial activity was measured based on the Minimum Inhibitory Concentration (MIC) of S. cordiformis ethanol extract against Staphylococcus aureus ATCC 25923. Paper disks containing the extracts of S. cordiformis in several concentrations were placed on agar and the inhibition zones were measured. Antifungal activity was also measured based on the MIC of the S. cordiformis ethyl acetate extract against Candida albicans ATCC 10231. Each measurement is carried out in triplo. Result: Ethanol extract of S. cordiformis with concentrations of 50% and 100% showed strong inhibition responses (12.25 mm and 16.42 mm).Concentrations of S. cordiformis Ethyl acetate extract of 3000 mg/mL and 6000 mg/mL have moderate inhibition responses (9.58 mm and 5.42 mm). Conclusion: Semele cordiformis used in this study have potency as an antibacterial and antifungal. Further invastigation involving isolation of more specific bioactive compound of the extract need more research